Poetics of Visibility / Poetics of Absence: Body and Theatricality (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This essay explores theatricalities of memory in which the body appears as an articulating axis central to various forms of struggle in the defense of human rights in Chile. We analyze a variety of scenes and theatricalities that find in the body an anchor for the constitution of demands for truth and justice trough various forms where representations of the absent body work as a central element for the reconstruction of memory. A wide range of theatricalities of memory allow us to reconstruct a narrative grounded on a poetics of the body on stage and organized around notions of presence/absence are expressed in the tensions between a poetics of visibility and a poetics of absence.
Keywords: Theatricalities of Memory; Body; Collective Memory; Human Rights.